Study of structural capacity in reinforced concrete beam by adding real-set 233 as an additive - Noor Hanisya, Mohammad Noor (2017)
This research aims to determine the structural capacity in reinforced concrete beam by adding REAL-SET 233 as concrete admixture when the concrete cracks in tension. This study points out two objectives, namely to determine the load-displacement of concrete and the strain-stress of steel bars in reinforced concrete beam which adding REAL-SET 233 as concrete admixture. This has be done by making a number of concrete mixes each with different amount of REAL-SET 233 admixture added to the concrete mix. The ratios of admixture that used in this study are 150 ml and 175 ml per m3 of concrete from the basic concrete grade C25/30. An experimental approach that has been taken in this study is Magnus Frame Four Point Test. There are 9 beams are provided with different mix proportion of concrete in this study. The size of the beam is 150 mm x 200 mm x 1500 mm. There are also provided 9 cubes with dimension size of 150 mm x 150 mm x 150 mm to get the average results of the compressive strength. From the analysis of data, it clearly shows that the use of REAL SET-233 admixture in concrete can be widely used in the construction industry and will have a major impact on the concrete technology industry in the future.